Cell metabolism sets the differences between subpopulations of satellite cells (SCs) - Repele, Andrea (BioMed Central, 2013)
BACKGROUND: We have recently characterized two distinct populations of Satellite Cells (SCs) that differ in proliferation, regenerative potential, and mitochondrial coupling efficiency and classified these in Low Proliferative Clones (LPC) and High Proliferative Clones (HPC). Herewith, we have investigated their cell metabolism and individuated features that remark an intrinsic difference in basal physiology but that are retrievable also at the initial phases of their cloning. RESULTS: Indeed, LPC and HPC can be distinguished for mitochondrial membrane potential (ΔΨ(m)) just after isolation from the fiber. This is matched by mitochondrial redox state measured via NAD(+)/NADH analysis and alternative respiratory CO(2) production in cloned cells. All these parameters are accountable for metabolic differences reflected indeed by alternative expression of the glycolytic enzyme 6-phosphofructo-2-kinase/fructose-2,6-biphosphatase 3 (Pfkfb3). Also Ca(2+) handling by mitochondria is different together with the sensitivity to apoptosis triggered via this pathway. Finally, according to the above, we were able to determine which one among the clones represents the suitable stem cell. CONCLUSIONS: These experimental observations report novel physiological features in the cell biology of SCs and refer to an intrinsic heterogeneity within which their stemness may reside.